2010
DOI: 10.1038/modpathol.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2: A biomarker significantly overexpressed in high-grade ovarian serous carcinoma

Abstract: Ovarian carcinoma consists of a group of histologically heterogeneous diseases involving distinct tumorigenic pathways. High-grade papillary serous carcinoma of the ovary is commonly associated with p53 mutations. HMGA2, an oncofetal protein, is found to be overexpressed in ovarian cancer. To study the function of HMGA2 in ovarian cancer, it is important to know which subtypes of ovarian cancer are associated with HMGA2 overexpression. In this study, we collected six different types of ovarian cancer and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 24 publications
(31 reference statements)
5
78
3
Order By: Relevance
“…11,25 We propose that MIR182 overexpression in high-grade serous ovarian carcinoma may be in part or completely responsible for HMGA2 overexpression. Although MIR182 and HMGA2 overexpression are found in nearly 70% of high-grade serous ovarian carcinoma (this study and Mahajan et al 16 and Wei et al 17 ), low correlation of expression of these two genes was found (r ¼ 0.23) in this study. This could be due to the fact that HMGA2 can be regulated by many microRNAs, such as the wellcharacterized ones in the let-7 family.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…11,25 We propose that MIR182 overexpression in high-grade serous ovarian carcinoma may be in part or completely responsible for HMGA2 overexpression. Although MIR182 and HMGA2 overexpression are found in nearly 70% of high-grade serous ovarian carcinoma (this study and Mahajan et al 16 and Wei et al 17 ), low correlation of expression of these two genes was found (r ¼ 0.23) in this study. This could be due to the fact that HMGA2 can be regulated by many microRNAs, such as the wellcharacterized ones in the let-7 family.…”
Section: Discussioncontrasting
confidence: 65%
“…This could be due to the fact that HMGA2 can be regulated by many microRNAs, such as the wellcharacterized ones in the let-7 family. 26,27 Nevertheless, we found HMGA2 overexpression is significantly associated with high-grade serous ovarian carcinoma 16 in this study (Table 4).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…MDM2 transcription level was inhibited when the P53 activation ,this block the apoptosis of tumor cells [6,7]; But whether HMGA2 can be combined with P53, no studies have reported. However, studies have found, HMGA2 in invasive ovarian cancer tissue was significantly correlated with the expression level of P53, the progress of the process involved in ovarian cancer [8], it suggesting that HMGA2 may affect P53 expression .…”
Section: Discussionmentioning
confidence: 99%